2021
DOI: 10.1080/1360144x.2021.1910953
|View full text |Cite
|
Sign up to set email alerts
|

How do I know who I am? Academic professional development, peer support, and identity for practitioners who teach

Abstract: Workplace preparation is increasingly part of university curricula and this has led to the appointment of staff with professional practice expertise being appointed to teach, who are experienced professionals yet HE novices. How do they make sense of HE's expectations and begin to reconcile their identity as educators with the credibility their practice expertise confers? The paper draws on sociocultural perspectives of Communities of Practice, framing identity development as a process of intertwined trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The data was collected using semi‐structured interviews, which made it possible to collect data flexibly and freely decide the order of the questions (Beaton, 2021). A pilot interview was conducted with one of the teacher‐practitioners who met the sampling criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data was collected using semi‐structured interviews, which made it possible to collect data flexibly and freely decide the order of the questions (Beaton, 2021). A pilot interview was conducted with one of the teacher‐practitioners who met the sampling criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that as experienced professionals, higher education novices differ from traditional early career academics, yet the challenges of the transition to a dual role are underexplored (Beaton, 2021). Not much is known about how practitioners experience their new identity in their academic career, why the career may be interrupted and how their identity as teachers is experienced afterwards.…”
mentioning
confidence: 99%